2007
DOI: 10.1111/j.1365-263x.2006.00806.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of paracetamol, ibuprofen or their combination for pain relief following extractions in children under general anaesthesia: a randomized controlled trial

Abstract: This study provides evidence to support the oral administration of ibuprofen alone or in combination with paracetamol for postoperative analgesia in children who are having teeth extracted under GA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
50
2
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 23 publications
5
50
2
10
Order By: Relevance
“…6891113 Ibuprofen has the advantage of a well-established safety record (particularly at doses below 1.5 g per day in adults), 14 and in many countries (including the UK), it is available without prescription. Typically, acetaminophen is given in a dose regimen of 1 g 6 hourly whereas ibuprofen is given in a dose of 400 mg 8 hourly.…”
mentioning
confidence: 99%
“…6891113 Ibuprofen has the advantage of a well-established safety record (particularly at doses below 1.5 g per day in adults), 14 and in many countries (including the UK), it is available without prescription. Typically, acetaminophen is given in a dose regimen of 1 g 6 hourly whereas ibuprofen is given in a dose of 400 mg 8 hourly.…”
mentioning
confidence: 99%
“…Furthermore, none of the published studies were performed in the ED; they were all conducted in the post-operative period [41]. Compared with paracetamol alone, the combination of paracetamol and ibuprofen was better for dental extraction [33] and tonsillectomy [42]. No study has compared NSAIDs alone versus a combination of paracetamol and an NSAID.…”
Section: Oral Paracetamol and Nsaid Combinedmentioning
confidence: 96%
“…Eleven other studies found no significant differences [30]. Ibuprofen was superior to paracetamol to increase comfort in febrile children [31], after musculoskeletal trauma [32], following dental extraction [33][34][35], and for the treatment of headaches [36]. Of interest to children in the ED, ibuprofen was not superior to paracetamol in the treatment of sore throat [37,38] or pain associated with illness [39].…”
Section: Oral Paracetamol or Non-steroidalmentioning
confidence: 99%
“…To date, there is limited but promising evidence to support the practice of combining acetaminophen and ibuprofen for pain treatment in children. [20][21][22][23][24] As noted by others, there remains a need for large-scale studies on both the efficacy and safety of this combination for the treatment of pain. 20 When asked to choose their preferred oral analgesic, respondents showed a strong preference for ibuprofen over acetaminophen.…”
Section: Discussionmentioning
confidence: 99%